Pengaruh Mechanical Bonding pada Aluminium dengan Serat Karbon terhadap Kekuatan Tarik Fiber Metal Laminates - Firmansyah, Hilmi Iman; Purnowidodo, Anindito; Setyabudi, Sofyan Arief (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2018)
Fiber metal laminates (FML) are composite structures fabricated by combining two layers of surface material with the core material. The outer surface of FML used in this composite is Aluminum with Al 1100 type. The FML core material uses carbon fiber. The fabrication process of the composites utilizes vacuum infusion method, in which the resin is infused into the mold with a vacuum condition. Bonds between the core and the surface layers are the variables affecting the strength of FML. In this research, the method used to increase the bonds between layers in FML was a mechanical method, it?s called mechanical bonding. This method involved providing roughness (Ra) on the aluminum surface using sandblasting process to produce different roughness variables, with roughness value of 1,68 ?m; 1,78 ?m; 1,93 ?m; 2,128 ?m and 2,887 ?m. The aim of this study was to examine the effect of aluminum surface roughness to the tensile strength of fiber metal laminates composites. The highest tensile strength of FML was obtained at 2,887 ?m with a value of 367 MPa.